Cell free Regenerative Medicine (RM) strategies for cartilague and bone put to the test in the challenging equine in vivo model - Vindas Bolaños, Rafael Ángel (2019)
This thesis focuses on in vivo studies in horses for the long-term evaluation of various regenerative approaches for articular cartilage and bone repair using cell-free techniques. It is concluded that the equine stifle joint and the tuber coxae represent reliable models to study the regeneration of cartilage and bone, respectively, in a truly translational sense, as they yield highly valuable information on potential for clinical use both in horses and humans. The high costs (both financially and in terms of animal welfare and ethics) of this work are justified by the vast economic and welfare needs of both humans and horses suffering from osteoarthritis (OA), for whom more effective treatments to aid the regeneration of cartilage and bone are urgently sought in order to improve their quality of life.